Culture and Emotion: The Work of the Women of Highlander Center - Colleen McDermott (Adult Education Research Conference, 2010)
The purpose of this study was to uncover the roles of the women of Highlander Research and Education Center. In this paper. I focus upon the influence of these women as cultural workers and caregivers. Robnett’s (1997) concept of bridge leader provided the theoretical framework for data analysis.